Cover Crop Biomass Removal Rates to Optimize Livestock Production and Soil Health in Dryland Cropping Systems - Logan Simon; Zachariah Carson; Augustine Obour; Frank Weber; Stacie Minson; Craig Dinkel (Kansas Agricultural Experiment Station Research Reports, 2025)
Grazing cover crops (CCs) could provide an economic benefit to offset potential lost revenue when grain crop yields are decreased after CCs in dry years. However, there is limited guidance on the optimum biomass removal rate that balances soil health and grazing goals. An on-farm study was established in fall 2022 on a 50-acre producer field in Russell County, KS, to investigate the effects of CC biomass removal with cattle grazing on soil health parameters and grain crop yields, and profitability in no-till (NT) dryland cropping systems. The study design was a randomized complete block with three treatments and four replications. The treatments included ungrazed CCs, take-half-leave-half (T-H-L-H, 50% biomass removal), and graze-out (G-O, 90% biomass removal). Averaged across 2023-2024, the T-H-L-H and G-O significantly reduced CC residue amount, height, and residue cover when compared to ungrazed CCs. Cover crop management had no significant effect on soil organic carbon and particulate organic matter. However, phosphorus (P) concentrations were reduced by T-H-L-H and G-O when compared to ungrazed CCs, likely due to purposefully avoiding sampling near manure piles in the grazed plots that may be high in P. Take-half-leave-half and G-O also increased soil bulk density compared to ungrazed CCs. Soil penetration resistance, wind-erodible fraction, mean weight diameter of water-stable aggregates, time-to-runoff, and subsequent grain sorghum yields were unaffected by CC management. These results suggest that farmers and ranchers may be able to graze CCs at greater intensities than T-H-L-H to maximize livestock gains while maintaining soil health. This can increase adoption of CCs and benefit water quality protection and improvement efforts in reaching the goals of the approved 9 Element Watershed Plan through the Kansas Department of Health and Environment and the Environmental Protection Agency. However, these observations were made in a two-year study and under exceptional drought conditions, so further investigation will be necessary under conditions of average or above average precipitation when wet soils may be more susceptible to soil compaction by cattle hoof traffic.
Keywords: cover crops; livestock; residue cover; soil health